Circulating miR-141-3p, miR-143-3p and miR-200c-3p are differentially expressed in colorectal cancer and advanced adenomas (2019)
Colorectal cancer (CRC) is one of the prominent causes of cancer related deaths because, in part, there is not an early, non-invasive, effective detection strategy. Circulating microRNAs (miRNAs) have been proposed as potential non-invasive biomarkers for CRC. In this study, we evaluated the miRNA profile in sixteen CRC tissues by Next‑Generation‑Sequencing and compared the circulating expression levels of 22 miRNAs among 45 CRC, 14 hyperplastic polyps, 11 advanced adenoma patients and 45 control subjects, by reverse transcription‑quantitative PCR, to search for miRNAs which could be potential biomarkers. In total, nine of them represented 70% of total read counts (miR‑10a‑5p, miR‑192‑5p, miR‑10b‑5p, miR‑22‑3p, miR‑26a‑5p, miR‑148a‑3p, miR‑181a‑5p, miR‑92a‑3p and miR‑143‑5p). In silico analysis found eight candidates to mature miRNAs. With respect to circulating miRNA, we found higher serum expression levels of miR‑143‑3p, miR‑141‑3p and miR‑200c‑3p in the CRC and adenoma groups compared with controls (P<0.002), and we also found significant higher levels of miR‑141‑3p and miR‑200c‑3p in serum of adenoma patients compared with the CRC group. In conclusion, the measurement of miRNAs in the blood could complement current screening methods for CRC and might provide new insights into mechanisms of tumorigenesis. miR‑143‑3p, miR‑141‑3p and miR‑200c‑3p could be interesting miRNAs to study as potential biomarkers for CRC.